Perancangan Sistem Informasi Pembelian Stok Barang dan Pencatatan Stok Barang Masuk Berbasis Microsoft Excel (Studi Kasus pada TB Sumber Agung) - Panggabean, Airlangga Dwitama Putra (Ebiz Prima Nusa, 2023)
Information systems for purchasing and recording inventory of incoming goods are important for companies in carrying out their business activities. Purchase flow system and record incoming goods stock at TB. Sumber Agung is still less effective and efficient. Thus, this can result in errors, delays, and even losses for the company. Therefore, the design of an information system for purchasing stock of goods and recording incoming stock of goods is made to facilitate and provide a positive impact for the company. In addition, the use of manual records for inventory is also not very effective and efficient. Microsoft Excel can be useful for companies to record goods in TB. Sumber Agung. Thus, the performance of employees and the company's business is more effective and efficient which results in companies getting greater profits and practicality in working at TB. Sumber Agung.